Inhibitory effect of Japanese rice-koji miso extracts on hepatitis A virus replication in association with the elevation of glucose-regulated protein 78 expression - Win, Nan Nwe (Int J Med Sci, 2018)
Hepatitis A virus (HAV) infection is one of the major causes of acute hepatitis and acute liver failure in developing and developed countries. Although effective vaccines for HAV infection are available, outbreaks of HAV infection still cause deaths, even in developed countries. One approach to control HAV infection is prevention through diet, which can inhibit HAV propagation and replication. Glucose-regulated protein 78 (GRP78) is a member of the heat shock protein 70 family of molecular chaperone required for endoplasmic reticulum stress and stress-induced autophagy. We previously showed that the elevation of GRP78 expression inhibits HAV replication. It has been reported that Japanese miso extracts, which was made from rice-koji, enhance GRP78 expression. In the present study, we used human hepatoma Huh7 cells and human hepatocyte PXB cells to examine the efficacy of Japanese miso extracts as antiviral agents against HAV. Japanese miso extracts enhanced GRP78 expression and inhibited HAV replication in human hepatocytes. Together, these results demonstrate that Japanese miso extracts may partly modulate GRP78 expression and additively or synergistically work as antivirals against HAV infection. Japanese miso extracts can be used as effective dietary supplements for severe hepatitis A.